Temporary architectures inside static architectures - Claudi de Saint Mihiel, Alessandro (TECHNE - Journal of Technology for Architecture and Environment, 2020)
The circumstances that produce architecture have profoundly changed and, among these, precisely those which perceive and use space-time in a different way in comparison with the past. This paper defines a conceptual reference framework by positioning the time factor in relation to the role of the project as an innovative and operational procedural tool in terms of sustainable conversion of cities. The essay aims to investigate the “addition strategy” as a paradigm of architectural grafting to achieve a balanced relationship between temporariness and permanence. It outlines scenarios in which a new design culture is capable of guiding the processes of transformation of the built environment by placing the idea of impermanence in a perspective that is closer to the current socio-technical condition.